Politicamente (in)correto: a reescrita e ressignificação de canções infantis - Schlemmer, Neosane (2022)
In the present study, we are dedicated to understanding the discourse considered politically (in)correct in rewritings and resignifications of children's songs, which in contemporary times have begun to circulate more frequently in social media and on the web. The use of the structure politically (in)correct is seen, in our work, as an indication that certain situations of language use, when verbalized, cause certain effects of meaning that come to characterize certain groups or social classes (SALACHE; VENTURINI, 2013) and, in view of this, not always a discourse that was the target of "correction" can be seen as really politically correct. This study aims to understand, at the same time, the place occupied by the subject about what is already said, what is seen as politically incorrect, as well as the space it covers to be the subject of what it says, which becomes politically correct. Thus, our research issue was established in the direction of the following question: what is the relationship between popular songs for children and the politically (in)correct language, in face of the interpretation gestures invested by the subjects that build (their) versions of popular songs for children, in a process of (de)construction of discourses? Based on this, we selected, as corpus of this research, eleven children's songs that circulated in social media, eight of them in Portuguese and three in Spanish, anchoring ourselves, in our analysis, to the theoretical and methodological apparatus of Discourse Analysis, henceforth AD, of French matrix. Therefore, our analyses allow us to observe that the effects of meaning conveyed by popular songs for children in Portuguese often print effects of erasure, because there is a removal of content considered incorrect. In a large minority, some songs, in their rewrites, recognize the harmful impact that the discourse present in their original versions had and, thus, take up again words already said, through a polysemic process and reiterate the form of representation of the songs, which are children's classics, many of them, known worldwide. As a closing effect, the effects of meaning that work in the face of a certain search for precision in making an incorrect song correct, cause an illusion of control over the meanings and, therefore, transform the correct into politically (in)correct. In relation to discontinuity, present by the effect of polysemy, it makes the political work in the language, in a gesture of interpretation of the composing subjects, which meets a struggle for rights, even if this is a process that alters the linguistic, seeking through language, through the song, through the voice of the subject that enunciates and becomes a subject when singing, the re-signification of the imaginary that one has about certain social groups that are marginalized and stereotyped.